Gap Analysis Kinerja Sistem Manajemen Lingkungan terhadap ISO 14001:2015 PT XYZ - Citra Nur Izati; Nurhasanah Nurhasanah (Yayasan Literasi Sains Indonesia, 2026)
The implementation of an Environmental Management System based on ISO 14001:2015 is a strategic instrument for improving environmental performance, operational efficiency, and regulatory compliance. This study aims to analyze the level of conformity of the Environmental Management System implementation at PT XYZ with the ISO 14001:2015 standard based on internal audit results using a gap analysis approach. The study employed a quantitative descriptive method with gap analysis of data obtained from the ISO 14001:2015 audit checklist. The analysis was conducted by comparing the actual implementation conditions of each clause with the standard requirements and subsequently classifying them according to their level of conformity. The results indicate that the implementation of the Environmental Management System generally falls within the moderately compliant category across most clauses. The highest levels of conformity were found in resource provision (100%), the scope of the Environmental Management System (87.5%), and risks and opportunities (87.5%). However, a significant gap was identified in the aspect of roles, responsibilities, and authorities (33.3%), which was categorized as poorly compliant. In addition, regulatory compliance, environmental objectives, monitoring, and internal audits each achieved a conformity level of 50%, indicating that their implementation has not yet been carried out consistently.